2020
DOI: 10.2147/ott.s276239
|View full text |Cite
|
Sign up to set email alerts
|

<p>To Develop and Validate the Combination of RNA Methylation Regulators for the Prognosis of Patients with Gastric Cancer</p>

Abstract: Background Gastric cancer (GC) accounts for high mortality. RNA methylation has recently gained interest as markers in specific tumors. This study aimed to uncover the function of the roles of 25 RNA methylation regulators in GC. Methods RNA sequence and clinical data were downloaded from The Cancer Genome Atlas (TCGA) database. “STRING” and R were performed to analyze the correlation among the methylase. COX and LASSO were performed to screen for prognostic associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The performed analysis of m5C and hm5C regulators based on gene expression levels in PRAD patients pinpointed a strong positive correlation among TET enzymes, which was also reported in earlier studies conducted in gastric cancer [74] and HNSCC [75]. Findings of positive correlation among DNMT enzymes, and between TET3 and DNMT3A genes support the previous results in HNSCC [75] and non-small cell lung carcinoma [76].…”
Section: Discussionsupporting
confidence: 87%
“…The performed analysis of m5C and hm5C regulators based on gene expression levels in PRAD patients pinpointed a strong positive correlation among TET enzymes, which was also reported in earlier studies conducted in gastric cancer [74] and HNSCC [75]. Findings of positive correlation among DNMT enzymes, and between TET3 and DNMT3A genes support the previous results in HNSCC [75] and non-small cell lung carcinoma [76].…”
Section: Discussionsupporting
confidence: 87%
“…As the fourth most common cancer worldwide, gastric cancer is a major cause of cancer-related death[ 1 ]. Currently, the number of new gastric cancer cases reported globally accounts for 5.7% of all cancer cases, with 8.2% of patients dying as a result[ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…found RBM15 is part of the WTAP-METTL3 N6-methyladenosine (m6A) methyltransferase complex and participates in M6A modification ( 64 ). Studies on RNA methylation regulators in papillary thyroid carcinoma (PTC) and gastric cancer have shown that RBM15 was significantly positively correlated with a better prognosis ( 65 , 66 ). But in LUAD, the high expression level of RBM15 is related to a poor prognosis ( 67 , 68 ).…”
Section: Rbm Proteins Family Can Use As a Predictor For A Prognosis Of Cancermentioning
confidence: 99%